2013
DOI: 10.1186/1471-2164-14-509
|View full text |Cite
|
Sign up to set email alerts
|

KEGG orthology-based annotation of the predicted proteome of Acropora digitifera: ZoophyteBase - an open access and searchable database of a coral genome

Abstract: BackgroundContemporary coral reef research has firmly established that a genomic approach is urgently needed to better understand the effects of anthropogenic environmental stress and global climate change on coral holobiont interactions. Here we present KEGG orthology-based annotation of the complete genome sequence of the scleractinian coral Acropora digitifera and provide the first comprehensive view of the genome of a reef-building coral by applying advanced bioinformatics.DescriptionSequences from the KEG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(48 citation statements)
references
References 491 publications
1
47
0
Order By: Relevance
“…Genes such as CCaMK that play a role in the establishment of rhizobial symbiosis between the legume plants and fungi (Mitra et al, 2004) were found to be conserved in symbiotic dinoflagellates (Table 6) and represented by several isoforms organized into two evolutionarily distant groups (Figure 3). They have, however, also been discovered in nonsymbiotic photosynthetic dinoflagellates like Karenia brevis, playing a role in intracellular signaling pathways (Lidie et al, 2005), as well as in the coral host (Shinzato et al, 2011;Dunlap et al, 2013) where they play a role in the motility of coral sperm (Morita et al, 2009). Interestingly, CCaMKs have been highly conserved in plants that establish rhizobial symbiosis with nitrogen-fixing soil bacteria, but not in nonleguminous plants such as Arabidopsis and wheat that do not have this type of symbiotic interaction (Mitra et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Genes such as CCaMK that play a role in the establishment of rhizobial symbiosis between the legume plants and fungi (Mitra et al, 2004) were found to be conserved in symbiotic dinoflagellates (Table 6) and represented by several isoforms organized into two evolutionarily distant groups (Figure 3). They have, however, also been discovered in nonsymbiotic photosynthetic dinoflagellates like Karenia brevis, playing a role in intracellular signaling pathways (Lidie et al, 2005), as well as in the coral host (Shinzato et al, 2011;Dunlap et al, 2013) where they play a role in the motility of coral sperm (Morita et al, 2009). Interestingly, CCaMKs have been highly conserved in plants that establish rhizobial symbiosis with nitrogen-fixing soil bacteria, but not in nonleguminous plants such as Arabidopsis and wheat that do not have this type of symbiotic interaction (Mitra et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, contigs 4300 nt in length were aligned, using the Translated Nucleotide-Protein BLAST application (BLASTx, version 2.2.27 þ ) and an E-value of p10 À 5 , to the SwissProt (SP) protein (version 2011_08), TrEMBL (version 2012_07) and National Center for Biotechnology Information (NCBI) nonredundant protein sequence (nr; 13 August 2011 update) databases for the purpose of annotation. Additional BLAST comparison of individually targeted sequences was carried out against an EST database (http://sequoia.ucmerced.edu/SymBioSys/) and the coral proteome database, ZoophyteBase (Dunlap et al, 2013). These databases include sequences of various cnidarian species and Symbiodinium strains.…”
Section: Assembly Assessment and Annotationmentioning
confidence: 99%
“…For more distantly related organisms, the use of HMM profiles as in the MEGGASENSE core analysis will yield better results. This was important for the ZoophyteBase for the proteome of the coral Acropora digitifera (27). In this case, the identification of functions together with the assignment of KEGG BRITE categories and the use of the Solr search engine allowed the development of novel hypotheses concerning functions such as interaction with symbiotic organisms.…”
Section: Discussionmentioning
confidence: 99%
“…A similar process was used to construct the ZoophyteBase database (http://bioserv7.bioinfo.pbf. hr/Zoophyte/registration/login.jsp) from the proteome of the coral Acropora digitifera (27). The search functions and the hierarchical KEGG BRITE classification allow the recognition of particular functions as well as collections of functions belonging to particular pathways.…”
Section: Simple Proteome Databasesmentioning
confidence: 99%
“…KEGG pathway analysis was conducted according to Li and colleagues (Dunlap et al, 2013). The sequences of identified proteins were queried against KEGG GENES (http://blast.…”
Section: Kegg Analysismentioning
confidence: 99%